UP male college student's consumption of beauty products and vanity services - Rivera, Ma. magdalena Sara
This study describes the consumption of UP male college students' consumption of beauty product and vanity services through the kinds and brands usually purchased and availed, frequency of purchasing and availment, location of availment, current prices of products purchased, and major influences for purchasing the said products and services. Responses were 76 University of the Philippines, Diliman male college students randomly selected regardless of age and course. Through self-administered questionnaires, data was analyzed through frequency, ranking, and percentile. Results show that UP male students now constitute a major part of the beauty care market. The top three beauty care products most purchased are: Facial Wash, Hair Styling Products, and Hair Conditioner. The top product brands for these products are: Master, Pond's, Nivea for Men, Gatsby, Bench, Creamsilk, Clear and Pantene. Meanwhile, vanity services most availed are: Bodybuilding, Nail Treatments, Facial Treatments, and Hair Removal Treatments. Hair removal and facial treatment services are availed mostly at Let's Face It and Bruno's, and Fitness First. Beauty Care products are mostly purchased 1 to 3 times a month while vanity services are availed either 1 to 3 times a month or 1 to 3 times in a year. Only weightlifting is done more often, 1 to 3 times a week. The study also showed that products are not necessarily the ones most purchased. Among the given influential factors that males purchase beauty products and avail vanity services, health is the most influential.